Student Self-Medication Behavior in Stress Handling - Risna Agustina; Ronny Lesmana; Neily Zakiyah; Siti Nuriyatus Zahrah; Ajeng Diantini (Journal of Tropical Pharmacy and Chemistry, 2022)
Changing learning patterns from senior high school student to college student status is difficult, and each individual's response varies, some of which cause stress. Factors that cause stress are internal and external, and external factors consist of physical, conflict, emotional, and behavioral conditions. In comparison, the external factors consist of the physical environment, work environment, community environment, family environment, economic and legal problems. The burden of life stress is heavy and impacts the physical, such as feeling dizzy, nauseous, ulcers, and difficulty sleeping. Sometimes causes a person to take self-medication to overcome these uncomfortable symptoms. This study aims to determine the characteristics of early-level students and the stress level of early-level students at one of the State Universities of East Kalimantan Province. This study used a qualitative descriptive design on 121 students. Using a questionnaire through a cross-sectional approach with a purposive sampling technique. The results showed that the stress level of students showed mild stress as much as 30.58%, moderate stress at 56.20%, and severe stress as much as 13.22%. The number of students who did self-medication was more than those who did not provide treatment for the symptoms, 79.34%.